2021
DOI: 10.1055/a-1499-0030
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab Dosing in Children and Adults with Hemophilia A: Simulating a User-Friendly and Cost-Efficient Regimen

Abstract: Background: When emicizumab is dosed according to label, clinicians are obligated to discard or overdose medication due to discrepancies between calculated dose and vial content. The aim of this study was to compose a cost-efficient emicizumab maintenance dosing regimen using Monte Carlo simulation based on vial size, patient friendly intervals and patient characteristics, while striving for similar plasma concentrations as observed in clinical trials. Methods: Monte Carlo simulations were used to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…the other suggests an alternative dosing regimen based on vial size and injection interval. 49 As yet, of the NRTs that may be effective in haemophilia B, none is licensed.…”
Section: Non-replacement Therapy (Nrt)mentioning
confidence: 99%
See 2 more Smart Citations
“…the other suggests an alternative dosing regimen based on vial size and injection interval. 49 As yet, of the NRTs that may be effective in haemophilia B, none is licensed.…”
Section: Non-replacement Therapy (Nrt)mentioning
confidence: 99%
“…Both studies used Monte Carlo simulations and concluded that rounding the dose is possible and results in cost savings 48,49 . One study refers to an online resource that can help identify the optimum dose 48 ; the other suggests an alternative dosing regimen based on vial size and injection interval 49 …”
Section: Recommendations and Suggested Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research pharmacists of the SYMPHONY consortium will provide a PK-guided dose advice based on a maximum a posteriori (MAP) Bayesian analysis of the individual observed concentration using an online platform https://opticlot.nl 21 22. MAP Bayesian will be performed using NONMEM software (V.7.4.1, Icon Development Solutions, Gaithersburg, Maryland, USA).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Also, in the Netherlands, Bukkems et al 91 reported an alternative simulated dosing regimen, with a target median emicizumab plasma concentration between 40 and 60 µg/mL at steady state. The authors reported that costs were saved in up to 60% of the virtual population and could reach a median of almost 60 000 euros.…”
Section: Isth 2021 Virtual Congressmentioning
confidence: 99%